Low Intensity Physical Exercise Attenuates Cardiac Remodeling and Myocardial Oxidative Stress and Dysfunction in Diabetic Rats - C. Gimenes; R. Gimenes; C. M. Rosa; N. P. Xavier; D. H. S. Campos; A. A. H. Fernandes; M. D. M. Cezar; G. N. Guirado; A. C. Cicogna; A. H. R. Takamoto; M. P. Okoshi; K. Okoshi (Journal of Diabetes Research)
We evaluated the effects of a low intensity aerobic exercise protocol on cardiac remodeling and myocardial function in diabetic rats. Wistar rats were assigned into four groups: sedentary control (C-Sed), exercised control (C-Ex), sedentary diabetes (DM-Sed), and exercised diabetes (DM-Ex). Diabetes was induced by intraperitoneal injection of streptozotocin. Rats exercised for 9 weeks in treadmill at 11 m/min, 18 min/day. Myocardial function was evaluated in left ventricular (LV) papillary muscles and oxidative stress in LV tissue. Statistical analysis was given by ANOVA or Kruskal-Wallis. Echocardiogram showed diabetic groups with higher LV diastolic diameter-to-body weight ratio and lower posterior wall shortening velocity than controls. Left atrium diameter was lower in DM-Ex than DM-Sed (C-Sed: 5.73±0.49; C-Ex: 5.67±0.53; DM-Sed: 6.41±0.54; DM-Ex: 5.81±0.50 mm; P<0.05 DM-Sed vs C-Sed and DM-Ex). Papillary muscle function was depressed in DM-Sed compared to C-Sed. Exercise attenuated this change in DM-Ex. Lipid hydroperoxide concentration was higher in DM-Sed than C-Sed and DM-Ex. Catalase and superoxide dismutase activities were lower in diabetics than controls and higher in DM-Ex than DM-Sed. Glutathione peroxidase activity was lower in DM-Sed than C-Sed and DM-Ex. Conclusion. Low intensity exercise attenuates left atrium dilation and myocardial oxidative stress and dysfunction in type 1 diabetic rats.